Analysis of Regional Medical Supply and Demand Network Characteristics Based on “Patient Flow Phenomenon”: A Case Study of the Core Area of the Wuhan Metropolitan Area - Fang Guo; Wei Wei; Bowen Xiang; Mengyao Hong (Land, 2024)
Examining medical supply–demand imbalances, as revealed through patients’ cross-boundary treatment behaviors, is vital for reducing a metropolitan area’s medical supply–demand gap and furthering sustainable development goals. This study, leveraging medical supply–demand and commuting data, scrutinizes medical imbalances in the Wuhan metropolitan area core. It includes a ‘People-centered’ theory for elucidating patients’ treatment behaviors, proposes a method for constructing a regional medical supply–demand network, and explores the problem of supply–demand imbalance. The key findings include: (1) Wuhan’s central area, despite its abundance of quality medical resources, fails to adequately cover the entire metropolitan area, indicating a need for broader resource distribution. (2) The Ezhou–Huangshi–Huanggang junction shows a stark contrast to Wuhan with its limited medical services and extensive hinterland connections. Future initiatives should aim to integrate resources dispersed from Wuhan, reducing regional disparities. (3) The city’s periphery, influenced by resource distribution models and geographic distance, exhibits significant variance from central urban areas in medical supply–demand connectivity, particularly around Wuhan’s eastern administrative boundaries. Future urban planning is needed to reinforce this area’s role as a vital medical services conduit. (4) The distinguishing differences among the nine medical service communities in terms of resource recognition, service sharing, and patient mobility provide policy guidance for the allocation of medical resources.